2021
DOI: 10.1002/art.41600
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals Interacting Key Determinants of Osteoarthritis Acting in Subchondral Bone and Articular Cartilage: Identification of IL11 and CHADL as Attractive Treatment Targets

Abstract: Objective. To identify key determinants of the interactive pathophysiologic processes in subchondral bone and cartilage in osteoarthritis (OA).Methods. We performed RNA sequencing on macroscopically preserved and lesional OA subchondral bone from patients in the Research Arthritis and Articular Cartilage study who underwent joint replacement surgery due to OA (n = 24 sample pairs: 6 hips and 18 knees). Unsupervised hierarchical clustering and differential expression analyses were conducted. Results were combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Recently, another study observed about 10% overlapping DEGs in OA cartilage and subchondral bone. They identified IL11 and CHADL as two potential therapeutic targets of OA by comparing their identified cartilage-subchondral bone overlapping DEGs with previously identified OA risk genes ( Styrkarsdottir et al, 2018 ; Tuerlings et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another study observed about 10% overlapping DEGs in OA cartilage and subchondral bone. They identified IL11 and CHADL as two potential therapeutic targets of OA by comparing their identified cartilage-subchondral bone overlapping DEGs with previously identified OA risk genes ( Styrkarsdottir et al, 2018 ; Tuerlings et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This year saw several genomics studies examining other tissues of the joint and investigating the relationships between joint tissues. Tuerlings et al examined subchondral bone using RNA sequencing (RNA-seq) to highlight the differentially expressed genes between paired preserved and lesional regions in 18 KOA and 6 HOA patients 29 . Comparison to articular cartilage revealed shared altered genes between joint sites, including the OA susceptibility genes IL11 and CHADL, which are candidates for future studies in in vivo OA models.…”
Section: Transcriptomics and Proteomicsmentioning
confidence: 99%
“…In healthy bones, a balance exists between bone resorption and deposition in response to dynamic adaptation to mechanical loading. In Osteochondral Defects (OCD), this balance is disrupted, leading to changes in the structure of the subchondral trabeculae (T bone), including increased thickness of the subchondral bone plate, formation of new bony structures at the joint edges (osteophytes), and development of subchondral bone cysts (Goldring and Goldring, 2010;Loeser et al, 2012;Funck-Brentano and Cohen-Solal, 2015;Tuerlings et al, 2021). Cartilage defects can be classified, using various methods, according to severity, width, and depth, according to different methods.…”
Section: Osteochondral Defectsmentioning
confidence: 99%